Implikasi Hukum Jual Beli Akun Pengemudi pada Layanan Jasa Taxi Online - Dyah Ochtorina Susanti; Siti Nur Shoimah (Universitas Islam Balitar, Blitar, 2019)
This research is motivated by the rise of selling and buying online taxi driver accounts that result in crimes by online taxi driver, such as sexual harassment, rape, robbery, and other crimes. This is certainly loss to the Passenger, so that the legal consequences of the sale and purchase action as intended. The results of the study using the normative legal research with the statute approach and conceptual approach is that which states that the sale and purchase of a driver's account on an online taxi service is a tort (PMH), and breaking tort which is arranged by Article 1365 Burgelijk Wetboek (BW) and brings losses to Passengers .